An improved method for mobile characterisation of δ13CH4 source signatures and its application in Germany - Hoheisel, Antje; Eckhardt, Henrik; Schmidt, Martina (Atmospheric measurement techniques, 2019)
The carbon isotopic signature (δ13CH4) of several methane sources in Germany (around Heidelberg and in North Rhine-Westphalia) were characterised. Mobile measurements of the plume of CH4 sources are carried out using an analyser based on cavity ring-down spectroscopy (CRDS). To achieve precise results a CRDS analyser, which measures methane (CH4), carbon dioxide (CO2) and their 13C-to-12C ratios, was characterised especially with regard to cross sensitivities of composition differences of the gas matrix in air samples or calibration tanks. The two most important gases which affect δ13CH4 are water vapour (H2O) and ethane (C2H6). To avoid the cross sensitivity with H2O, the air is dried with a Nafion dryer during mobile measurements. C2H6 is typically abundant in natural gases and thus in methane plumes or samples originating from natural gas. A C2H6 correction and calibration are essential to obtain accurate δ13CH4 results, which can deviate by up to 3 ‰ depending on whether a C2H6 correction is applied. The isotopic signature is determined with the Miller–Tans approach and the York fitting method. During 21 field campaigns the mean δ13CH4 signatures of three dairy farms (−63.9±0.9‰), a biogas plant (−62.4±1.2‰), a landfill (−58.7±3.3‰), a wastewater treatment plant (−52.5±1.4‰), an active deep coal mine (−56.0±2.3‰) and two natural gas storage and gas compressor stations (−46.1±0.8‰) were recorded.In addition, between December 2016 and November 2018 gas samples from the Heidelberg natural gas distribution network were measured with a mean δ13CH4 value of −43.3±0.8‰. Contrary to previous measurements between 1991 and 1996 by Levin et al. (1999), no strong seasonal cycle is shown.
Gesehen am 23.07.2019
Im Titel ist "13" hochgestellt und "4" tiefgestellt